2017
DOI: 10.4236/jcdsa.2017.72017
|View full text |Cite
|
Sign up to set email alerts
|

Situation of Artificial Depigmentation among Women in 2016 to Bobo-Dioulasso, Burkina Faso

Abstract: INTRODUCTION:The artificial depigmentation (DA) is a practice that aims to reduce the natural pigmentation of the skin by the use of depigmenting products (DP). In Burkina Faso, few studies have been made on the issue and the last date of 2003. The objective of the study is to realize an overview of the DA phenomenon in women population in Bobo-Dioulasso City. METHODS: This is a descriptive cross-sectional study held from April 16th to April 30th 2016 including 437 women aged from 13 to 55 years old. A multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…Another research, evokes change by focusing on the current era marked by the progression of voluntary depigmentation. This would concern two women out of three in Bobo-Dioulasso in 2016, contrary to the situation which prevailed about fifteen years ago (Andonaba et al, 2017). The other aspect of time as a change highlighted by this research is the fact that depigmentation presents itself in our study site as a set of unstable choices, practitioners often dropping their old products for new.…”
Section: Discussioncontrasting
confidence: 44%
“…Another research, evokes change by focusing on the current era marked by the progression of voluntary depigmentation. This would concern two women out of three in Bobo-Dioulasso in 2016, contrary to the situation which prevailed about fifteen years ago (Andonaba et al, 2017). The other aspect of time as a change highlighted by this research is the fact that depigmentation presents itself in our study site as a set of unstable choices, practitioners often dropping their old products for new.…”
Section: Discussioncontrasting
confidence: 44%
“…Another research, evokes change by focusing on the current era marked by the progression of voluntary depigmentation. This would concern two women out of three in Bobo-Dioulasso in 2016, contrary to the situation which prevailed about fifteen years ago (Andonaba et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…Its presence was mentioned on the labels of 24.12% of the collected products. Andonaba et al [5] found in 2019 that only 4.86% of skin-lightening cosmetics marketed in the city of Bobo-Dioulasso in Burkina Faso mentioned the presence of hydroquinone. Indeed, since 2001 there has been a ban on the use of hydroquinone in cosmetic products in Europe [28].…”
Section: Mentions Of the Presence Of Depigmenting Substances On Labelsmentioning
confidence: 99%
“…Its prevalence among women in Nigeria was estimated at 40.09% in 2021 [4]. In Burkina Faso, Andonaba et al reported a prevalence of 49.2% in the city of Bobo-Dioulasso in 2016 [5]. The prevalence in the city of Ouagadougou is lower and had been estimated in 2005 at 39.5% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation